Alternative Models of Food Buffer Systems for Large Cities in Indonesia - Ahmad, Ahfandi; Sulaiman, Andi Amran; Tarman, Risma Niswati (Tarjih : Agribusiness Development Journal, 2025)
Every country has efforts to fulfill food. In order to ensure a fair and equitable food supply at the community, household and individual levels in accordance with the purchasing power to meet food needs. Therefore, an alternative food buffer model is needed in each region, especially in big cities. This paper recommends a big city food buffer model with at least five areas that become the main functions of TTIC/DC. First, the field of supply management. Second, supply reserve management. Third, supply distribution management. Fourth, institutional management of food cooperation. Fifth, e-commerce-based information technology system. Food supply to big cities can be done by optimizing nearby areas to be more effective and efficient, and cutting long supply and distribution chains. This is important so that price fluctuations that often occur in big cities can be properly addressed.